Service delivery interventions to improve adolescents' linkage, retention and adherence to antiretroviral therapy and HIV care1. Issue 8 (13th May 2015) - MacPherson, Peter; Munthali, Chigomezgo; Ferguson, Jane; Armstrong, Alice; Kranzer, Katharina; Ferrand, Rashida A.; Ross, David A.
Abstract Objectives Adolescents living with HIV face substantial difficulties in accessing HIV care services and have worse treatment outcomes than other age groups. The objective of this review was to evaluate the effectiveness of service delivery interventions to improve adolescents' linkage from HIV diagnosis to antiretroviral therapy (ART) initiation, retention in HIV care and adherence to ART. Methods We systematically searched the Medline, SCOPUS and Web of Sciences databases and conference abstracts from the International AIDS Conference and International Conference on AIDS and STIs in Africa (ICASA). Studies published in English between 1st January 2001 and 9th June 2014 were included. Two authors independently evaluated reports for eligibility, extracted data and assessed methodological quality using the Cochrane risk of bias tool and Newcastle–Ottawa Scale. Results Eleven studies from nine countries were eligible for review. Three studies were randomised controlled trials. Interventions assessed included individual and group counselling and education; peer support; directly observed therapy; financial incentives; and interventions to improve the adolescent‐friendliness of clinics. Most studies were of low to moderate methodological quality. Conclusions This review identified limited evidence on the effectiveness of service delivery interventions to support adolescents' linkage from HIV diagnosis to ART initiation, retention on ART and adherence to ART. Although recommendations are qualified because of the small numbers of studies and limited methodological quality, offering individual and group education and counselling, financial incentives, increasing clinic accessibility and provision of specific adolescent‐tailored services appear promising interventions and warrant further investigation.